2000
DOI: 10.1614/0043-1745(2000)048[0385:tqrbwe]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The quantitative relationship between weed emergence and the physical properties of mulches

Abstract: Mulches on the soil surface are known to suppress weed emergence, but the quantitative relationships between emergence and mulch properties have not been clearly defined. A theoretical framework for describing the relationships among mulch mass, area index, height, cover, light extinction, and weed emergence is introduced. This theory is applied to data from experiments on emergence of four annual weed species through mulches of selected materials applied at six rates. Mulch materials, in order from lowest to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
392
3
7

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 416 publications
(414 citation statements)
references
References 16 publications
12
392
3
7
Order By: Relevance
“…This is supported by results from Sosnoskie et al (2012b) and Burgos and Talbert (2000) who found that allelopathic chemicals produced by cereal rye inhibit Palmer amaranth germination and seedling growth. Earlier studies have also shown that establishment of small-seeded weeds (of similar size to those of Palmer amaranth) is reduced by mulch residues (Mohler and Teasdale 1993;Teasdale and Mohler 2000). In the absence of PRE herbicides, early-season Palmer amaranth populations were reduced when cotton was planted into a strip-tillage rolled rye winter cover crop system, relative to the strip tillage winter fallow system (Timper et al 2011).…”
Section: Management Of Palmer Amaranthmentioning
confidence: 97%
“…This is supported by results from Sosnoskie et al (2012b) and Burgos and Talbert (2000) who found that allelopathic chemicals produced by cereal rye inhibit Palmer amaranth germination and seedling growth. Earlier studies have also shown that establishment of small-seeded weeds (of similar size to those of Palmer amaranth) is reduced by mulch residues (Mohler and Teasdale 1993;Teasdale and Mohler 2000). In the absence of PRE herbicides, early-season Palmer amaranth populations were reduced when cotton was planted into a strip-tillage rolled rye winter cover crop system, relative to the strip tillage winter fallow system (Timper et al 2011).…”
Section: Management Of Palmer Amaranthmentioning
confidence: 97%
“…However, the primary use of cover crops in organic ZT is to create vegetative mulch for weed suppression. As little as 2,700 kg ha −1 of above-ground dry matter produced by fall-seeded cover crops can suppress annual weed density the following spring and early summer by as much as 75% [26], although at least 7,000 kg ha −1 of residue may be needed to suppress annual broadleaf weeds by 80% [27]. Teasdale [26] concluded that cover crop residue could provide good early season weed suppression but that full-season weed control was not provided.…”
Section: Organic Zero Tillagementioning
confidence: 99%
“…The high biomass accumulated by triticale and white oats could have resulted in high maize grain yields obtained in the plots. Biomass of cover crops is known to affect subsequent crops by increase in nutrients, soil properties, moisture conservation and weed suppression (Teasdale and Mohler, 2000;Crandall et al, 2005). Winter cover crops could have had an effect on soil moisture, soil nutrition and weeds in the subsequent season.…”
Section: Discussionmentioning
confidence: 99%
“…White oats and triticale had the lowest weed dry weight due to high biomass from the cover crop species. Various cover crop species suppressed growing weeds as well as germinating weed seeds by modifying the conditions under which weeds germinate either by changing soil temperature, increase in soil moisture and physical impediment of weed seedlings (Teasdale and Mohler, 2000). White oats and triticale are also known to produce allellopathic chemicals (Weston, 1996), which might have played a role in suppression of weeds.…”
Section: Discussionmentioning
confidence: 99%